Optimizing Leg Muscle Strength of Pencak Silat Athletes through Plyometric Training (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of plyometric training on improving leg muscle strength in Pencak Silat athletes at Paguron GEPAK. The research employed an experimental method with a One Group Pretest-Posttest Design, which is classified as a quasi-experimental type. The sample consisted of 15 Pencak Silat athletes selected using a purposive sampling technique. The data collection instrument used was the Vertical Jump test (Miller, 2010), which measures lower-limb explosive power. The plyometric training program was conducted over six weeks with a frequency of three sessions per week, including exercises such as squat jumps, box jumps, lateral jumps, depth jumps, and standing broad jumps. Data were analyzed using a Paired Sample t-test with the assistance of SPSS version 26.0. The results showed a significant difference between the pretest and posttest scores of the Vertical Jump, with an average improvement of 16.33 cm. The calculated t-value was -6.336 with a significance level of 0.000 (< 0.05), indicating that plyometric training had a significant effect on increasing leg muscle strength. It can be concluded that plyometric training is effective in enhancing leg muscle strength and explosive power among Pencak Silat athletes. The improvement occurred due to neuromuscular and mechanical adaptations resulting from the Stretch Shortening Cycle (SSC) principle in plyometric exercises. Therefore, this training program is recommended as part of physical conditioning to improve explosive performance in Pencak Silat athletes.